The best short stories 2025 : the O. Henry Prize winners - Berry, Wendell, 1934-; Chung, Gina, 1989-; Citchens, Addie E., 1980-; Deagler, Michael; Drager, Lindsey; Edgerton, Clyde, 1944-; Eggers, Dave; ffitch, Madeline, 1981-; Finch, Indya; Hoffman, Alice; Kalu, Jane; Korsgaard, Thomas, 1995-; et al. (Vintage Books, 2025)
"Continuing a century-long tradition of cutting-edge literary excellence, this year's edition contains twenty prizewinning stories chosen from the thousands published in magazines over the previous year. Guest editor Edward P. Jones has brought his own refreshing perspective to the prize, selecting stories by an engaging mix of celebrated names and emerging voices. The winning stories are accompanied by an introduction by Jones, observations from the winning writers on what inspired them, and an extensive resource list of magazines that publish short fiction."--